Landmark-based morphometric and meristic variations of freshwater garfish, Xenentodon cancila from four natural stocks of South-Western Bangladesh - Mahfuj, Md Sarower E; Rahman, Md Motiur; Islam, Monirul; Samad, Md Abdus; Paul, Alok Kumar; Adhikary, Ripon Kumar (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The morphometric and meristic variations of Xenentodon cancila was studied based on the landmark-based truss network system to assess their phenotypic variations among four different freshwater stocks, viz. Boluhorpur baor, Jhenaidah (BBJ) (n = 29); Bhairab River, Jashore (BRJ) (n = 34); Arial Khan River, Madaripur (AKRM) (n = 28), and Bohnni baor, Gopalganj (BBG) (n = 25) in Bangladesh. Materials and methods: Seven meristic characters were counted by using a needle. Eight morphometrics and 28 truss measurements were measured by using tpsDigV.2.1 software. In meristic characters, Kruskal–Wallis test was performed to determine any significant differences, whereas, in morphometrics and truss measurements, univariate statistics and discriminant function analyses were carried out by using SPSS 22 version. Results: Significant differences were observed in four meristic characters among seven meristic characters in the Kruskal–Wallis test. In univariate statistics, only nine characters were observed significantly different among eight morphometrics and 28 truss measurements. The contribution of three discriminant function analyses (DFA), in which first DFA showed 49.2%, second DFA showed 33%, and third DFA showed 17.8% on behalf of both morphometric and truss measurements. In discriminant space, the four stocks were clearly separated. Two clusters were formed among four stocks, where BBG formed a single cluster, whereas BBJ and BRJ aggregately formed another cluster. Additionally, AKRM formed a sub-cluster with BBJ. Conclusion: The preliminary information generated from the current study would be beneficial for further genetic studies and in the assessment of ecological impacts on X. cancila stocks in Bangladesh. J. Adv. Vet. Anim. Res., 6(1): 117-124, March 2019